Exploring the sport-alcohol relationship: a longitudinal qualitative study of student-athlete drinking following the transition out of university - Jankowski, M.; Partington, S.; Heather, N.; Partington, E. (Journal of Clinical Sport Psychology, 2024)
The purpose of this study was to provide new knowledge about the temporal and contextual aspects of the alcohol-sport relationship. Eight U.K. student-athletes completed the Alcohol Use Disorders Identification Test in their final year at university, 18 months, and 30 months after graduation. They also completed semistructured interviews about their drinking motives, behaviors, and life circumstances. Results showed that participants reduced their alcohol consumption after leaving university, but despite the onset of some adult responsibilities, most were still drinking at hazardous levels. After university, drinking took place with old friends, new colleagues, and new sporting teammates. At all time points, social drinking motives were the most prevalent. Findings demonstrate a relationship between alcohol and sport that is cemented at university but continues beyond it. Targeted interventions to reduce the role of alcohol in the social experience of sport are needed to support long-term athlete health.